Radiation sensitive integrated detectors based on compounds AIIBVI - Галат, А. Б.; Гашин, П. А.; Гринев, Б. В.; Старжинский, Н. Г.; Зеня, И. М. (ХНУРЕ, 2007)
Methods are considered of preparation of photosensitive structures nZnSe(Te)–pZnTe and ZnSe(Te)/pZnTe–nCdSe using solid-phase substitution reactions and subsequent epitaxial growth on crystals ZnSe(Te) . It has been shown that maximum e.m.f. value for integrated detectors is 1,2-1,4 V, and their X-ray sensitivity reaches values up to 150-200 nAmin/Rcm2.
Keywords: scintillators; radiation; detector